Procedimento para definição de políticas de manutenção de via permanente ferroviária - Seraco, Isaias Pereira (2019)
This work proposes a procedure for the definition of railroad track maintenance policies or programs, having as main objective to establish the frequency with which services must be performed so that the corresponding costs are the lowest possible in the long term. The development of this work is based on the study of the behavior that costs of both geometric maintenance and track renewal acquire in various configurations of maintenance programs, by exploring the interference relation that the track geometric condition has on the rate at which its components degrade. The proposed method analyzes how several distributions of maintenance processes, along the useful life of a railway segment, impact on the track lifecycle cost, making it suitable to define the service arrangement that represents lowest-cost maintenance policy. This procedure is a tool to support the long-term planning, aiming to provide managers with the necessary subsidies for the correct programming of maintenances according to the prerogatives of performance and safety. Its use is applicable to any railway and permanent way configuration.